Factors contributing to outbreaks of food poisoning in England and Wales 1970-1979. - Roberts, D. (Cambridge University Press, 1982)
Epidemiological data accompanying reports of more than 1000 outbreaks of food poisoning have been studied to determine the factors which most frequently contributed to the outbreaks. Preparation of food in advance of needs combined with improper storage and inadequate cooking, cooling and reheating were the most common factors. Infected food handlers did not play a significant role except in instances of S. aureus food poisoning.